SECURITY ANALYSIS BETWEEN STATIC AND DYNAMIC SBOXES IN BLOCK CIPHERS - Nur Hafiza Zakaria; Azuan Ahmad; Azni Haslizan Ab Halim; Farida Hazwani Mohd Ridzuan, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2021)
The development of block ciphers has resulted in a number of cryptographic algorithms such as AES, aria, blowfish256, desl, and 3d-aes. AES is one of the best cryptographic algorithms that can be used to protect electronic data. However, the principal weakness in AES is the linearity in the s-box. The objective of this research is to investigate and evaluate the existing work related to the dynamic s-box. Other than that, the aim of this research is to design a dynamic s-box using affine transformation in order to increase the security of the encryption. The method to design is using java with the NetBeans software. The proposed block cipher will be tested using NIST statistical test suite to test the randomness of the algorithm. Besides, the strength of the s-box will be analyzed using the s-box evaluation tool (set). The cryptographic strength depends strongly on the choice of s-box. Therefore, this new proposed block cipher can be used by countries, organizations, stakeholders, or interested parties as one of the secure algorithms to increase the protection of the information and also will contribute as an alternative to other cryptographic algorithms in computer security research.